The endoplasmic reticulum as a most efficient antibody factory - Sitia, Roberto (Henry Stewart Talks, 2007)
Studies on the synthesis, assembly and secretion of antibodies during B cell development reveal fundamental properties of the endoplasmic reticulum as a protein factory, How do cells regulate the formation, isomerisation and reduction of disulfide bonds?, How do plasma cells manage to secrete massive amounts of antibodies?, Is antibody production somehow controling plasma cell lifespan?, Answers to these questions have profound implications in biotechnology and medicine, as they may help design better bioreactors for the production of recombinant proteins and better therapies for multiple myeloma and other secretory tumors
Archived at 2021/02/25